Diversity of Fusarium spp. on Various Host Plants in Indonesia: a Systematic Review - Seftyana, Avi Sheila; Sukma, Pawesti Ramadhini; Nuraeni, Sifa; Sari, Indah Juwita; Mumtazah, Najwa Qonita (Universitas Brawijaya, 2025)
This study systematically reviews the diversity of Fusarium spp. associated with various host plants in Indonesia, including banana, shallot, taro, maize seeds, and weeds. Fusarium is a major group of pathogenic fungi in agriculture, capable of infecting multiple plant parts such as roots, stems, and leaves. The review also considers both pathogenic and endophytic species, as well as the influence of environmental factors on their occurrence. Data were synthesised from ten relevant articles obtained through the Google Scholar database. The findings indicate that environmental factors—particularly humidity, temperature, and host plant availability—play a significant role in shaping the diversity of Fusarium spp. in Indonesia. These insights can support the development of effective management strategies to prevent the spread of Fusarium and promote the sustainability of agricultural ecosystems.